Issues and perceptions of environmental reporting in Singapore. - Chong, Jie Min. (2008)
This paper studies the environmental disclosure in corporate annual reports in Singapore. It also strives to investigate any differences between the desired and actual level of environmental disclosure in the annual reports. One motivation for this study is the increasing awareness and regulations of environmental matters both worldwide and Singapore.